2023
DOI: 10.1186/s40813-023-00326-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genetic characterization of enteric viruses in diarrhoea outbreaks from swine farms in Spain

Abstract: Background The aim of this work was to study the prevalence and distribution of Porcine astrovirus (PAstV), Porcine kobuvirus (PKoV), Porcine torovirus (PToV), Mammalian orthoreovirus (MRV) and Porcine mastadenovirus (PAdV) as well as their association with widely recognized virus that cause diarrhoea in swine such as coronavirus (CoVs) and rotavirus (RVs) in diarrhoea outbreaks from Spanish swine farms. Furthermore, a selection of the viral strains was genetically characterized. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In this study, we identified 9 DEGs (Galnt 1–5, 7, 10–12) following RVA and RVC infection. Among them, expression of six [ 3 5 , 7 , 11 , 12 ] genes was significantly modulated. The most prominent effect (downregulation) on the expression of these enzymes was observed for GALNT5 in PIEs infected with RVC and G9P[13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified 9 DEGs (Galnt 1–5, 7, 10–12) following RVA and RVC infection. Among them, expression of six [ 3 5 , 7 , 11 , 12 ] genes was significantly modulated. The most prominent effect (downregulation) on the expression of these enzymes was observed for GALNT5 in PIEs infected with RVC and G9P[13].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is growing evidence that species C RV (RVC) is a significant cause of infectious diarrhea in humans and animals [ 4 7 ]. While RVAs mostly affect piglets or young children after weaning [ 8 , 9 ], RVC diarrhea is highly prevalent among nursing, 1–10-day-old piglets, causing significant economic losses to farmers and the pork industry [ 4 , 10 , 11 ]. Recent data suggest that reassortant RVC strains circulate in northeast Asia in both the human and swine populations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As leading causes of swine diarrhea, PEDV, RVA, PDCoV and/or TGEV are frequently characterized on worldwide pig farms [ 15 , 16 ]. It is of clinical significance to develop rapid and accurate multiplex methods to differentiate these four agents from diarrheal causes as the symptoms induced by them are similar [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate investigation, Sachsenröder and colleagues demonstrated that the proportion of porcine viruses in the intestinal virome decreased with increasing pig age, whereas the opposite was observed for phages [ 14 ]. This suggests a potential correlation between the porcine enteric virome and age [ 15 , 16 ]. Nonetheless, there is still a gap in the research on the intestinal virome of weaned Tibetan pigs.…”
Section: Introductionmentioning
confidence: 99%